Lingvo-Cultural phenomenon and Newspaper Headline - Mikadze, Manana ("Intercultural Dialogues" Transactions, 2023)
Presented Paper is dedicated to highlighting Newspaper Headline, i.e. Forerunning text, being one of the contracted forms of Newspaper Information which has an informative function. Newspaper headline aims at informing the reader in short about the coming Article. English Newspaper Headline is distinguished by its laconic nature, beyond which much more information is hidden. It includes a system of interrelated lexical, phraseological and grammatical means serving the purpose of informing, instructing and, in addition, of entertaining the reader. Not all the printed matter found in newspapers comes under newspaper style. The modern newspaper carries material of an extremely diverse character. On the pages of a newspaper one finds not only news and comments on it, but also stories and poems, crossword puzzles, and the like. Since these serve the purpose of entertaining the reader, they cannot be considered specimens of newspaper style. Nor can articles in special fields, such as science and technology, art, literature, etc. be classed as belonging to newspaper style. Since the primary function of a newspaper is to impart information, only printed matter serving this purpose comes under newspaper language variety. Mostly Newspaper Headlines include such Linguistic Units which require relevant Lingvo-Cultural Knowledge of the reader to correctly perceive and understand it. Thus, Newspaper Headline can be analyzed not only as a pure linguistic as well as Cultural Phenomenon which must be viewed from Lingvo-Cultural point. Presented Paper once again emphasized the utmost importance of Lingvo-Cultural Factor for correct perception and decoding of Newspaper Headline. Hence it is necessary to have relevant socio-cultural knowledge around the subject provided within the Headline as well as analyzing from Lingvo-Cultural viewpoint.